An applied printing immunoassay with recombinant Nc-SAG1 for detection of antibodies to Neospora caninum in cattle - Wilkowsky, Silvina Elizabeth (2011)
Neospora caninum is a protozoan parasite that causes an important reproductive disease in cattle. Neospora caninum surface antigen 1 (Nc-SAG1) is an immunodominant candidate for the development of a diagnostic reagent for neosporosis. The current study describes the development and evaluation of an antigen print immunoassay (APIA) with recombinant Nc-SAG1 for the detection of specific antibodies to N. caninum in cattle. The concordance between APIA and a commercial enzyme-linked immunosorbent assay (ELISA) was evaluated with 232 serum samples from experimentally and naturally infected cattle. Sixty-one (26.7%) samples were positive for antibodies to N. caninum by ELISA and 58 (25.4%) by APIA. The new assay had a sensitivity of 85% and a specificity of 96%. These results, along with the potential of APIA to evolve into a multiple antigen detection format, suggest that this method would be a reliable diagnostic test for detection of antibodies to N. caninum in cattle.